Strategy of Analysis of Handling Human Smuggling In The Malacca Strait By Armada 1 - Roestiawan, Dwi Bagus; Ridlo, Ali; Zahari, Abdul Kadir Mulku (IJOSMAS, 2024)
Human smuggling is a form of transnational crime involving individuals or groups to facilitate the movement of illegal immigrants across national borders, either in an organized or unorganized manner. Immigrants who are often victims of armed conflict or war use land and sea routes to seek protection in their destination countries. The Strait of Malacca as one of the most important international shipping lanes in the world is an area that is vulnerable to being used as a route for human smuggling. Koarmada I has a strategic role in maintaining the security of the Strait of Malacca, especially in combating human smuggling. The strategies used include deploying troops at sea, coordinated patrols with neighbouring countries, and Indonesian Navy diplomacy. Obstacles in implementing this strategy include the very large operational area, limited intelligence information, and the absence of special standard operating procedures for handling illegal immigrants at sea. This study uses a qualitative methodology with the Nvivo application with the aim of analysing the strategy for handling human smuggling in the Strait of Malacca implemented by Koarmada I. The results of the study are expected to provide relevant recommendations for the development of more effective strategies in efforts to maintain national security. This approach is also expected to improve cooperation between the Indonesian Navy and relevant stakeholders to face the challenges of human smuggling in the Malacca Strait region.